Interpretación de pruebas de pulso mediante la técnica TDS (2018)
Well testing is the cheapest way to characterize a reservoir. A well test is often used as the principal technology to monitor either the investment performance of such systems or for unexpected well or reservoir diagnostic behaviors. the results of the well test data analysis are used to make the decisions that lead to a good project management. Well test provide the information to establish the reservoir characteristics, predicting the operation of the reservoir and diagnosing the damage of the information. The pulse test is a special form of multiple well testing initially described in 1966. The technique uses a short rate pulse series in the active well. The pulses are usually alternating periods of production or injection and closing, with the same rate during each period of production or injection. The pressure response of the pulses is measured in the observation well. Due to the pulse is of short duration, the pressure response is small, sometimes less than 0.01 psi. Therefore, a special equipment for measuring pressure is usually required. The most popular interpretation methodology for pulse testing is the tangent method which requires plotting the pressures against time data and drawing a tangent between two continuous valleys or peaks and a parallel to the peak between them. The main disadvantage of this method lies in the use of previously designed correcting charts which make the analysis cumbersome. This study presents the analysis of pulse testing in hydrocarbon reservoirs using the log-log graph of the pressure and pressure derivative function versus time at the observer well so a technique that uses characteristics points and features on the mentioned plot is developed to find the interwell permeability of porosity of the reservoir. Finally, synthetic examples are presented with the purpose of verifying the equations reliability, finding that the calculated are very accurate.